2022
DOI: 10.3390/cancers14122861
|View full text |Cite
|
Sign up to set email alerts
|

IFI35 Promotes Renal Cancer Progression by Inhibiting pSTAT1/pSTAT6-Dependent Autophagy

Abstract: Interferon-induced protein 35 (IFI35), is currently acknowledged to govern the virus-related immune inflammatory responses. However, the biological significance and function of IFI35 in renal cell cancer (RCC) is still not well understood. Here, IFI35 expression and function were investigated in RCC tissues, renal cancer cells, and animal models. The results showed that IFI35 expression was significantly increased in 200 specimens of RCC patients. We found that higher IFI35 levels were significantly correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Autophagy works as a crucial role in the tumors cell goes, since it can inhibit tumor growth in early stages of tumors and promote the occurrence and metastasis of cancer in late stages of tumors (Choi, 2012). Previous studies had shown enhanced STAT1/ STAT6 phosphorylation (pSTAT1/pSTAT6)-dependent autophagy can suppress the proliferation and invasion of RCC cells (Chai et al, 2022). The induction of autophagy can also help RCC cells resist the killing effect of immune cells, which is an essential reason for the unsatisfactory effect of immunotherapy in RCC (Messai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy works as a crucial role in the tumors cell goes, since it can inhibit tumor growth in early stages of tumors and promote the occurrence and metastasis of cancer in late stages of tumors (Choi, 2012). Previous studies had shown enhanced STAT1/ STAT6 phosphorylation (pSTAT1/pSTAT6)-dependent autophagy can suppress the proliferation and invasion of RCC cells (Chai et al, 2022). The induction of autophagy can also help RCC cells resist the killing effect of immune cells, which is an essential reason for the unsatisfactory effect of immunotherapy in RCC (Messai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%